Pulse jet engine / Mohd Hairie Hazali - Hazali, Mohd Hairie (2004)
As a final year project the group decided to design, fabricate and test a pulse jet engine. The design was targeted to produce 6 pounds of thrust. As there is no design guidelines or textbook material regarding pulse jet engine available for references, it was decided that data of historically functional pulse jet engines was collected and empirically correlated. The data collected include produced thrust, dimension of pulse jet engine components (viz. Tailpipe length, diameter) and valve area. All components were desgined and fabricated from scratch. The pulse pulse jet engine was succesfully assembled. Testing was carried out using different fuels. The pulse jet failed to ignite with kerosene and petrol due to the difficulty in getting the correct proportion of fuel air mixture. Subsequently liquefied petroleum gas (LPG) was selected based on its wider flammability limits. After repeated toiling with different design parameters such as reed valve design and angle of reed valve retainer, the pulse jet engine was finally successfully started. However, the engine can only run continously under constant supply of air from a vaccum cleaner. This can be sustained for about 15-20 seconds berfore the front of the engine caught fire. This was due to leakage of heat from the reed valve to the mixing index core of the engine.